Stability estimates for yield in maize cultivars for the State of Minas Gerais - Coelho, Antônio Marcos; Morais, Augusto Ramalho de; Gama, Elto Eugenio Gomes e; Silva, Bernardo Gonçalves da; Cornélio, Wanda Maria de O. (Pesquisa Agropecuaria Brasileira, 2014)
Yield stability of 28 hybrids, four intervarietal hybrids and four open pollinated varieties was studied at twelve environments in the State of Minas Gerais, Brazil. The cultivars Cargill 115, Dekalb 678, Cargill 525, Germinal 15C, Cargill 111 S and Cargill 511 A showed the best yielding performance. In accordance to the stability parameter (b) the cultivars Germinal 491, Germinal 493, CMS 12, Cargill 203, Pioneer 3218, Pioneer 3216, Pioneer 6875 and Agroceres 352 F showed high yield stability. According to regression deviation (S2d), Germinal 493, Cargill 511 A, Pioneer 3216 and Agroceres 302 showed the least values. The cultivars Cargill 511 A, Pioneer XCH 36 and Agroceres 303 were the best for yield stability for all three parameters. The open pollinated varieties CPJ VI and CMS 12, CMS 06 and IAC Maya XXI were more and less stable to environmental response, respectively.